Knowledge and attitude pertinent to COVID-19 and willingness to COVID vaccination among medical students of University College of Medicine & Dentistry Lahore - Javeria Usman , Ifrah Arshad , Anosha Fatima , Muhammad Ahsan , Namra Mina, (Journal of Rawalpindi Medical College, 2021)
Objectives: To determine the awareness and beliefs of medical students towards Corona disease and the COVID-19 vaccine and to assess the willingness to get vaccinated against COVID-19. Methods: This was a cross sectional study conducted on undergraduate medical students at University College of Medicine and dentistry, University of Lahore (UOL). A self-developed questionnaire containing demographic information, 8 knowledge and attitude items and 11 items for perceptions and willingness to get COVID-19 vaccine was completed by 410 participants. Results: More than ninety five percent of participants were aware of the cause, mode of transmission and mortality associated with corona disease; however, a handful of them knew about the purpose of using vaccine. Majority of the participants believed that COVID-19 vaccine will be effective and a good way to get protected from the disease. Regarding willingness to get cocid-19 vaccine, more than half of the participants wanted to be the first to get vaccinated but majority were concerned about the safety of COVID-19 vaccine. Conclusion: The medical students of University College of Medicine and dentistry, University of Lahore (UOL) displayed an adequate level of knowledge and awareness towards COVID-19 and a positive attitude about COVID-19 vaccine. Our study noted a high level of COVID-19 vaccine acceptance among medical students, yet there were significant concerns about the safety of vaccine.